Reversible contrast enhancement for visualization of human temporal bones using micro computed tomography - Bommakanti, Krishna K.; Iyer, Janani S.; Sagi, Varun; Brown, Alyssa; Ma, Xiaojie; Gonzales, Marissa; Stankovic, Konstantina M. (Frontiers in Surgery, 2022)
Sensorineural hearing loss (SNHL), which typically arises from the inner ear, is the most common sensory deficit worldwide. The traditional method for studying pathophysiology underlying human SNHL involves histological processing of the inner ear from temporal bones collected during autopsy. Histopathological analysis is destructive and limits future use of a given specimen. Non-destructive strategies for the study of the inner ear are urgently needed to fully leverage the utility of each specimen because access to human temporal bones is increasingly difficult and these precious specimens are required to uncover disease mechanisms and to enable development of new devices. We highlight the potential of reversible iodine staining for micro-computed tomography imaging of the human inner ear. This approach provides reversible, high-resolution visualization of intracochlear structures and is becoming more rapid and accessible.